A Review of Enterprise Risk Management Practices among Malaysian Public Listed Companies - Lai, Fong Woon (2012)
The risk sphere in business is fast changing and expanding. Almost anything has become a risk factor that will have potent, direct, and far reaching impacts on business. This paper examines the intensity of enterprise risk management (ERM) practices among the Malaysian public listed companies. The paper espouses a ERM framework comprising fourteen important implementation elements and processes. Results of the analysis indicate that the intensity of ERM implementation among the respondents is in the „good‟ category of the semantic scale, which is deemed encouraging vis-à-vis the country‟s regulatory regime.